DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Roderick Delano Chandra; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to determine empirically the effect of firm size, dividend policy, capital structure, profitability, and liquidity on firm value either partially or simultaneously. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018 to 2020. The sample selection method used is purposive sampling. The companies used as research objects are 42 companies out of a total of 168 companies. The research method used in this research is multiple linear regression analysis. The results obtained from this study are that liquidity has a negative and insignificant effect on firm value, capital structure and dividend policy have a positive and insignificant effect on firm value, profitability has a positive and significant effect on firm value, and firm size has a negative and significant influence on firm value.